2012
DOI: 10.5304/jafscd.2012.023.013
|View full text |Cite
|
Sign up to set email alerts
|

Community Engagement from the Ground Up: An Interdisciplinary Service-Learning After-School Garden Program

Abstract: Through the vehicle of community engagement, and with a commitment to ecological sustainability, the University of Georgia has made a series of efforts to support a growing local food movement through education, research, and service. This paper focuses on the development of a comprehensive after-school garden program with direct links to the university via interdisciplinary servicelearning mechanisms. The university is located in a county with one of the highest poverty rates in the nation. With a commitment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…However, this is beginning to change. Scholars are sketching the contours of a food systems pedagogy-an approach to teaching and learning about food that is interdisciplinary (Valley et al, 2017), that embraces complexity (Jordan et al, 2014), and that includes experiential learning opportunities (Levkoe et al, 2018;Miller et al, 2012). Importantly, scholars are insisting that critical food systems pedagogy must also be values-based (Galt et al, 2012, p. 43) and pose a challenge to the social and ecological injustice perpetuated by the contemporary industrial food system (Flowers & Swan, 2012;Sumner, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, this is beginning to change. Scholars are sketching the contours of a food systems pedagogy-an approach to teaching and learning about food that is interdisciplinary (Valley et al, 2017), that embraces complexity (Jordan et al, 2014), and that includes experiential learning opportunities (Levkoe et al, 2018;Miller et al, 2012). Importantly, scholars are insisting that critical food systems pedagogy must also be values-based (Galt et al, 2012, p. 43) and pose a challenge to the social and ecological injustice perpetuated by the contemporary industrial food system (Flowers & Swan, 2012;Sumner, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Based on this, school gardens can take advantage of it to source financial support from communities and relevant stakeholders. It is learned that without stakeholders' involvement in community projects, the project often fails (Miller et al 2012;Fischer et al 2019). For instance, parents and guardians could be invited to support wards in planting, watering, and weeding to increase community trust and social capital.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the positive contribution of school gardening to education and climate change adaption, some major challenges prevail which include limited resources (Fischer et al 2019;Greer et al 2019), limited space and staff (Burt et al 2018), funding and maintenance difficulties (Huys et al 2017;Nocito 2012), limited volunteer support and class time (Loftus et al 2017), disjointed communication (Miller et al 2012), inadequate staff training (Rich and Ardoin 2014), long explanations or instructions (Nury et al 2017), standards-based curricular materials and difficulties with an initial startup (Huys et al 2017). Additionally, recent studies have identified some common barriers militating against SGP in Africa, including inadequate staffing, limited time, low teacher interest or training, and challenges incorporating SGP into the curriculum (e.g., Laurie et al 2013;Sumberg et al 2017;Yu 2012).…”
Section: Introductionmentioning
confidence: 99%